Animals as objects and subjects of environmental criminal and misdemeanor law, with special reference to dogs - Vince Vári (Glasnik Advokatske komore Vojvodine)
The protection of animals plays a crucial role in the legal system related to environmental protection. Act C of 2012, effective from July 1, 2013, includes a dedicated chapter on protecting the environment and wildlife. Hungarian regulations on environmental liability encompass civil, administrative, misdemeanor, and criminal liability. This paper aims to present the fundamental legal aspects of protecting animals within environmental law. It focuses on legislation and practical issues falling under penal law, particularly concerning dogs. Environmental law regarding dogs is two-fold. Firstly, it protects animals from abusive behavior, whether physical or mental. Secondly, it involves situations where dogs become a part of environmental law, such as when they are released into public areas without proper supervision. The clear delineation of specific acts poses a challenge for law enforcement, emphasizing the need to clarify the legislative environment and its practical aspects.